Cognitive Linguistics: Its Past, Present and Future - Žic Fuchs, Milena (Array, 1995)
The aim of this paper was to show how Cognitive Linguistics developed from structuralism and in contrast to TG grammar. Special emphasis was put on possible future applications in language acquisition, translation, etc.